USE OF MODULAR RATING SYSTEMS IN THE STUDY OF FOREIGN LANGUAGES - Т.М. Husak; O.H. Malinko (Academy of Cognitive and Natural Sciences, 2000)
The present article deals with the question o f using module-rating system during foreign language learning process.